PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN PAJAK, DAN AKUNTABILITAS PELAYANAN PUBLIK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DENGAN VARIABEL INTERVENING PENDAPATAN - Khairunnisa Zahira Asri; Yeni, Fitri; Eliza (Universitas Prof.Hazairin,SH Bengkulu, 2024)
This study aims to determine the influence of taxpayer awareness, tax knowledge, and public service accountability on compliance of motor vehicle taxpayers with the income variable as an intervening variable at the Samsat Office in Sawahlunto City. This type of research is quantitative research. The sampling technique used Accidental Sampling. The number of sample respondents in this study was 100 respondents. Data collection technique used a questionnaire conducted at the Samsat Office in Sawahlunto City. The results of this study indicate that taxpayer awareness influences income, while tax knowledge and public service accountability do not influence income. Additionally, taxpayer awareness, tax knowledge, and income influence taxpayer compliance. Meanwhile, public service accountability does not influence taxpayer compliance. Income cannot mediate the influence of taxpayer awareness, tax knowledge, and public service accountability on compliance of motor vehicle taxpayers.